Application of collagen triple helix repeat containing‐1 and mitotic spindle apparatus antibody in small cell lung cancer diagnosis. Issue 5 (6th April 2022) - Liu, Yuhan; Hu, Tingting; Li, Xu; Li, Xiaohang; Yu, Jianlin; Wu, Yang; Chen, Simei; Tan, Liming
Abstract: Background: The clinical significance of serum collagen triple helix repeat protein‐1 (CTHRC1) and mitotic spindle apparatus antibody (MSA) in the diagnosis of small cell lung cancer (SCLC). Methods: Of the 229 lung tumor patients selected, 62 patients were divided into SCLC, 94 patients with non‐small cell lung cancer (NSCLC), and 73 patients with benign lung disease (BLD). The health controls (HC) had a span of 66 cases with normal physical condition. The serum extracted from each participator and enzyme‐linked immunosorbent assay was adopted for measuring the serum CTHRC1 and MSA; in the meantime, automatic electrochemiluminescence immunoassay was used for the quantitative determination of serum NSA and CEA. And then, the differences in serum CTHRC1, MSA, NSE, and CEA were compared among involved groups. Results: ① Compared with other groups, the concentrations of CTHRC1, MSA, and NSE showed a marked increase in the group of SCLC (all p  < 0.01). Especially for SCLC patients with lymph node metastasis, CTHRC1 provided a notably higher level than those without metastasis. ② CTHRC1 and MSA established a diagnostic criterion with the specificity of 90.99% and 86.27% for SCLC, respectively. ③ In series, the specificity of CTHRC1 and NSE was the highest (99.30%), while MSA and NSE had the highest sensitivity (96.72%) in parallel. ④ Both CTHRC1 and MSA were hazardous factors interconnected with SCLC. Conclusion: Serum CTHRC1 and MSA had a more exciting prospect of application. When used in conjunction with NSE and CEA, they could optimize the clinical diagnosis value of SCLC. Abstract : CTHRC1 and MSA are overexpressed in serum of SCLC patients, and the level of CTHRC1 can predict lymph node metastasis in SCLC. When CTHRC1 and MSA combined detection with classical tumor, serum markers such as NSE and CEA can ameliorate the sensitivity and specificity for the diagnosis of SCLC.